2016
DOI: 10.1002/jbm.a.35839
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrillar hydrogel scaffolds from recombinant protein‐based polymers with integrin‐ and proteoglycan‐binding domains

Abstract: This study describes the design, production, and testing of functionalized variants of a recombinant protein‐based polymer that forms nanofibrillar hydrogels with self‐healing properties. With a view to bone tissue engineering applications, we equipped these variants with N‐terminal extensions containing either (1) integrin‐binding (RGD) or (2) less commonly studied proteoglycan‐binding (KRSR) cell‐adhesive motifs. The polymers were efficiently produced as secreted proteins using the yeast Pichia pastoris and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 55 publications
(93 reference statements)
1
20
0
Order By: Relevance
“…The design and production in P . pastoris of the genetically engineered protein-based polymers C 2 S H 48 C 2 and B RGD C 2 S H 48 C 2 was described recently by us [ 19 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The design and production in P . pastoris of the genetically engineered protein-based polymers C 2 S H 48 C 2 and B RGD C 2 S H 48 C 2 was described recently by us [ 19 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, rheological analysis revealed that the gels exhibit strain stiffening and are able to self‐heal rapidly, even after repeated breaking cycles. Both effects (strain stiffening and self‐healing) resemble the behavior of natural collagen type I …”
Section: Silk Inspired Biomaterialsmentioning
confidence: 72%
“…At higher protein concentrations, a fibrous gel is formed, with stiffness depending on the polymer concentration. Reproduced with permission . Copyright 2016, Wiley Periodicals, Inc.…”
Section: Silk Inspired Biomaterialsmentioning
confidence: 99%
See 2 more Smart Citations